Pengaruh Efektivitas Penerapan E-bupot Unifikasi, Dan E-billing Terhadap Kinerja Bendaharawan Dalam Melaksanakan Pemotongan/Pemungutan Pajak Pada Dinas Pendidikan, Kepemudaan Dan Olahraga Provinsi Bali - Gede Arcana; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2023)
This research was conducted with the aim of knowing the effect of the Effectiveness of the Implementation of E-Bupot Unification, and E-Billing on the Performance of Treasurers in Implementing Tax Withholding/Collection at the Office of Education, Youth and Sports of the Province of Bali. The population in this study were school treasurers (boss fund treasurers/treasurers who operate the web and tax applications at schools) in the work units of the Bali Province Education, Youth and Sports Office. The number’s of sample in this study were 141 schools. The data in this study were obtained through the results of distributing questionnaires and were analyzed using multiple linear regression analysis techniques. Based on the result of testing the data thats has been carried out in this study, it was found that the application of e-bupot and e-billing had a positive and significant effect on taxpayer compliance. Based on the results of the research and the constraints encountered in this research, development is still needed to make this research better.